1994
DOI: 10.1128/mcb.14.4.2352
|View full text |Cite
|
Sign up to set email alerts
|

The novel primary response gene MyD118 and the proto-oncogenes myb, myc, and bcl-2 modulate transforming growth factor beta 1-induced apoptosis of myeloid leukemia cells.

Abstract: Cell numbers are regulated by a balance among proliferation, growth arrest, and programmed cell death. A profound example of cell homeostasis, controlled throughout life, is the complex process of blood cell development, yet little is understood about the intracellular mechanisms that regulate blood cell growth arrest and programmed cell death. In this work, using transforming growth factor beta 1 (TGF beta 1)-treated M1 myeloid leukemia cells and genetically engineered M1 cell variants, the regulation of grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
127
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(130 citation statements)
references
References 57 publications
2
127
1
Order By: Relevance
“…Furthermore, activation of an inducible MyD118 transgene in hematopoietic cells was observed to result in apoptotic M1 cell death (unpublished). Blocking the expression of MyD118 in M1 cells by an antisense vector was shown to impair TGFb induced cell death (Selvakumaran et al, 1994a). Furthermore, blocking TGF-b induced apoptosis in M1 cells due to ectopic expression of bcl-2, was associated with down regulation of MyD118 transcripts; in contrast, deregulated expression of c-myc or c-myb in M1, abrogating TGF-b-induced growth arrest and accelerating apoptosis, was associated with marked elevations in the level of MyD118 transcripts (Selvakumaran et al, 1994a).…”
Section: Myd116 ± Viral Homologs and A Protective Role In Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, activation of an inducible MyD118 transgene in hematopoietic cells was observed to result in apoptotic M1 cell death (unpublished). Blocking the expression of MyD118 in M1 cells by an antisense vector was shown to impair TGFb induced cell death (Selvakumaran et al, 1994a). Furthermore, blocking TGF-b induced apoptosis in M1 cells due to ectopic expression of bcl-2, was associated with down regulation of MyD118 transcripts; in contrast, deregulated expression of c-myc or c-myb in M1, abrogating TGF-b-induced growth arrest and accelerating apoptosis, was associated with marked elevations in the level of MyD118 transcripts (Selvakumaran et al, 1994a).…”
Section: Myd116 ± Viral Homologs and A Protective Role In Apoptosismentioning
confidence: 99%
“…Blocking the expression of MyD118 in M1 cells by an antisense vector was shown to impair TGFb induced cell death (Selvakumaran et al, 1994a). Furthermore, blocking TGF-b induced apoptosis in M1 cells due to ectopic expression of bcl-2, was associated with down regulation of MyD118 transcripts; in contrast, deregulated expression of c-myc or c-myb in M1, abrogating TGF-b-induced growth arrest and accelerating apoptosis, was associated with marked elevations in the level of MyD118 transcripts (Selvakumaran et al, 1994a). On the other hand, Gadd45 has been implicated in p53-mediated G1 cell cycle arrest following DNA damage (Kastan et al, 1992).…”
Section: Myd116 ± Viral Homologs and A Protective Role In Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Because Myb can also inhibit the di erentiation of hemopoietic cells (Selvakumaran et al, 1994;Todokoro et al, 1988;Yanagisawa et al, 1991;Clarke et al, 1988), it has been postulated that the e ect of Myb on cellular proliferation may be due to the regulation of c-myc transcription. Indeed, transactivation by Myb of the cmyc promoter (Evans et al, 1990;Nakagoshi et al, 1992;Zobel et al, 1992) and in one case, endogenous c-myc (Evans et al, 1990) has been reported.…”
Section: Apoptosis In Ermyb Cellsmentioning
confidence: 99%
“…HL-60 human promyelocytic leukemia cells induced to undergo maturation by retinoic acid ultimately die an apoptotic death, although as a relatively late event (Martin et al, 1990). However, di erentiation and apoptosis are mutually exclusive in other systems (Selvakumaran et al, 1994). Moreover, dysregulated maturation of U937 human leukemia cells (e.g., following enforced expression of protein kinase C-z) leads to apoptosis rather than di erentiation after treatment with phorbol myristate acetate (PMA) (de Vente et al, 1995).…”
mentioning
confidence: 99%